Multilayer circular substrate-integrated waveguide cavity band-pass filters with ultrawide stopband characteristics - Medda, Amrita; Azad, Amit Ranjan; Mohan, Akhilesh; Sinha, Manoranjan (International journal of microwave and wireless technologies, 2024)
This paper presents a methodology to design band-pass filters having ultrawide stopband characteristics using multilayer circular substrate-integrated waveguide (SIW) cavities. The orthogonal microstrip feedlines are used as input and output ports that are present at the top and bottom layers, while the middle layers are used to couple the SIW cavities. Higher-order spurious modes of the circular SIW cavity are suppressed by using orthogonal feeding mechanism and properly adjusting the arc-shaped slots between the cavities. To validate the present approach, two filters (second- and fourth-order) have been designed and fabricated and their characteristics are measured. The second-order filter exhibits a stopband rejection below 25 dB up to nearly 5.07f0, while the fourth-order filter has a stopband characteristic of nearly 5.05f0 with 20 dB rejection. The filters allow only TM010 mode propagation and attenuate the higher-order spurious modes of the cavity.